Prediction of Disease Genes Based on Stage-Specific Gene Regulatory Networks in Breast Cancer - Fan, Linzhuo; Hou, Jinhong; Qin, Guimin (Frontiers in Genetics, 2021)
Breast cancer is one of the most common malignant tumors in women, which seriously endangers women's health. Great advances have been made over the last decades, however, most studies predict driver genes of breast cancer using biological experiments and/or computational methods, regardless of stage information. In this study, we propose a computational framework to predict the disease genes of breast cancer based on stage-specific gene regulatory networks. Firstly, we screen out differentially expressed genes and hypomethylated/ hypermethylated genes by comparing tumor samples with corresponding normal samples. Secondly, we construct three stage-specific gene regulatory networks by integrating RNA-seq profiles and TF-target pairs, and apply WGCNA to detect modules from these networks. Subsequently, we perform network topological analysis and gene set enrichment analysis. Finally, the key genes of specific modules for each stage are screened as candidate disease genes. We obtain 7 stage-specific modules, and identify 20, 12 and 22 key genes for three stages, respectively. Furthermore, 55%, 83% and 64% of the genes are associated with breast cancer, for example E2F2, E2F8, TPX2, BUB1 and CKAP2L. So it may be of great importance for further verification.